Systems of Narrative Observation - Kadhim, Sameer Abbas (Al-Adab Journal, 2015)
Fiction is an imaginative discourse closely linked to the way the narrated worlds related to absence, comprising a truth producing means; it has the symbolic power that enables us to conceive the world around us in order to legitimize our human disposition for social existence. The different forms of conflict that abound the social life are not communicated directly but often mediated by another symbolic system that imposes its distinctive nature when interpreting the absent but decontextualized world. This mediation, which is based on the social transformations, imposes new ways of discursive production on imagination enabling fictional position, which includes the temporal and special contents, and its different narrative structures, to organize the expressive fluxes and determine the narrative distribution. In doing so, it is not only the narrator’s stereotypical characteristics that are conveyed to the narrated world, but also his own faculty for artistic expression.